Classical literature and learning in medieval Irish narrative - O'Connor, Ralph ca. 20./21. Jh (D.S. Brewer, 2014)
Examinations of the use of classical Latin texts, themes and techniques in medieval Irish narrative. This edited volume will make a major contribution to our appreciation of the importance of classical literature and learning in medieval Ireland, and particularly to our understanding of its role in shaping the content, structureand transmission of medieval Irish narrative. Dr Kevin Murray, Department of Early and Medieval Irish, University College Cork. From the tenth century onwards, Irish scholars adapted Latin epics and legendary histories into the Irish language, including the Imtheachta Aeniasa, the earliest known adaptation of Virgil's Aeneid into any European vernacular; Togail Troí, a grand epic reworking of the decidedly prosaic historyof the fall of Troy attributed to Dares Phrygius; and, at the other extreme, the remarkable Merugud Uilixis meic Leirtis, a fable-like retelling of Ulysses's homecoming boiled down to a few hundred lines of lapidary prose.Both the Latin originals and their Irish adaptations had a profound impact on the ways in which Irish authors wrote narratives about their own legendary past, notably the great saga Táin Bó Cúailnge (The Cattle-Raid of Cooley). The essays in this book explore the ways in which these Latin texts and techniques were used. They are unified by a conviction that classical learning and literature were central to the culture of medieval Irish storytelling,but precisely how this relationship played out is a matter of ongoing debate. As a result, they engage in dialogue with each other, using methods drawn from a wide range of disciplines (philology, classical studies, comparative literature, translation studies, and folkloristics). Ralph O'Connor is Professor in the Literature and Culture of Britain, Ireland and Iceland at the University of Aberdeen. Contributors: Abigail Burnyeat, Michael Clarke, Robert Crampton, Helen Fulton, Barbara Hillers, Máire Ní Mhaonaigh, Ralph O'Connor, Erich Poppe
Title from publisher's bibliographic system (viewed on 24 Feb 2023)
Keywords: Irish literature / Middle Irish, 1100-1550 / History and criticism; Classical literature / Appreciation / Ireland; Classical literature / Translations into Irish; Literatur; Latein; Irisch; Kultur; Aufsatzsammlung